Dare the Discipline(s) to Build a New Academy: The Future of Kinesiology and Health in Higher Education: National Association for Kinesiology in Higher Education 40th Dudley Allen Sargent Commemorative Lecture 2021. Issue 2 (3rd April 2021) - Clark, Langston
ABSTRACT: In the 40th Annual Dudley Allen Sargent Lecture, I dared the field of kinesiology with its various subdisciplines to be at the center of systematic and individual change in the values, behaviors, and functions of higher education. It is not meant to be a harsh critique of kinesiologists, but is rooted in the belief that the field of kinesiology is suited to be daring enough to build a new academy. Influenced by the work of progressive era educational scholar Howard Counts, I highlight five fallacies associated with the function of higher education, then provide five challenges to prompt our field to ontologically reimagine the academy.